Cardiotoxicity of Non Cardiovascular Drugs: A Mechanistic Point of View (BIRDEM Medical Journal, 2013)
Cardiotoxicity has evolved as an essential component of various adverse drug reactions and an important aspect in drug development and withdrawal. A triphasic interaction of the drug, its mechanism of action on the heart and various factors influencing toxicity is the basis of various cardiotoxicities. A comprehensive knowledge of the various mechanisms of cardiotoxicities and classes of drug causing it would promote appropriate drug selection, simultaneous use of cardioprotective drugs and work as a guideline for the development of new drugs and targeted therapies. A check in the drug causes of cardiotoxicities would definitely play a vital role in eliminating a significant fraction of the cardiovascular diseases and delay the rate and magnitude of the development of the impending cardiovascular disease epidemic. Birdem Med J 2013; 3(1): 35-43 DOI: http://dx.doi.org/10.3329/birdem.v3i1.17125